2002
DOI: 10.1034/j.1600-6143.2002.020210.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Risk of Elective Cyclosporine Withdrawal in Stable Kidney Transplant Recipients

Abstract: Although it is known that elective cyclosporine (CsA) withdrawal increases the risk for acute rejection, few studies have been large enough to identify risk factors for acute rejection after CsA withdrawal. We examined risk factors for acute rejection in 464 kidney transplant recipients who underwent elective CsA withdrawal. The incidence of acute rejection within 6 months of CsA withdrawal was 20/141 (14.2%) in the period January 1986 to May 1989, but only 14/323 (4.5%) since May 1989 (p = 0.0002). Among thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Future clinical trials are needed to study the impact of interventions that reduce the risk of CHD, NODAT, and also metabolic syndrome. Such trials could study the impact of steroid avoidance [35], CNI withdrawal [36], switching from CNIs to mTOR inhibitors [37], and higher doses of mycophenolate mofetil along with lower levels of CNIs, on modifying the risks of CHD, NODAT, and metabolic syndrome. Trials studying new agents that increase HDL cholesterol could test whether or not these agents modify the risks of CHD and metabolic syndrome [38].…”
Section: Discussionmentioning
confidence: 99%
“…Future clinical trials are needed to study the impact of interventions that reduce the risk of CHD, NODAT, and also metabolic syndrome. Such trials could study the impact of steroid avoidance [35], CNI withdrawal [36], switching from CNIs to mTOR inhibitors [37], and higher doses of mycophenolate mofetil along with lower levels of CNIs, on modifying the risks of CHD, NODAT, and metabolic syndrome. Trials studying new agents that increase HDL cholesterol could test whether or not these agents modify the risks of CHD and metabolic syndrome [38].…”
Section: Discussionmentioning
confidence: 99%
“…Anjum et al (17) reported an increased risk for patients with both two HLA-B and two HLA-DR mismatches. The measurement of the frequency of precursor cytotoxic T lymphocytes in the peripheral blood could allow identification of patients in whom minimization of immunosuppression can be achieved safely (9,18).…”
Section: Discussionmentioning
confidence: 99%
“…Although acute rejection occurred more frequently in patients electing CsA withdrawal, there was no difference in graft survival over nearly 6 years of follow-up compared with patients electing to remain on CsA. The risk of acute rejection was similar in patients treated with MMF, and those treated with AZA (4/67; 6% versus 26/314; 8%), although the small number of patients receiving MMF precludes drawing firm conclusions regarding the impact of these agents on acute rejection (41).…”
Section: Cni Withdrawal Regimensmentioning
confidence: 70%
“…Anjum et al (41) evaluated risk factors for acute rejection in a large cohort of stable renal transplant patients (nϭ464) undergoing voluntary CsA withdrawal. CsA withdrawal was begun 1 year after transplant/last rejection episode.…”
Section: Cni Withdrawal Regimensmentioning
confidence: 99%